Pengaruh Penggunaan Financial Technology, Media Sosial dan e-Commerce Terhadap Pendapatan UMKM di Kota Padang - Friska Novalista; Indrayeni (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the effect of financial technology, social media, and e-commerce on the income of Micro, Small, and Medium Enterprises (MSMEs) in East Padang District, Padang City, both partially and simultaneously. The research population consists of 181 MSME actors registered at the Cooperative and MSME Office of Padang City in 2025. The sample was selected using a simple random sampling technique so that each member of the population had an equal chance of being chosen. The research approach used is quantitative, with primary data obtained through questionnaires distributed to respondents. Data analysis includes multiple linear regression, coefficient of determination, t-test, and F-test, processed using SPSS version 26. The results show that financial technology has a positive and significant effect on MSME income, social media has a positive and significant effect on MSME income, and e-commerce has a positive and significant effect on MSME income. Simultaneously, financial technology, social media, and e-commerce have a positive and significant effect on MSME income in East Padang District. The contribution of the three independent variables to MSME income is 55.5%.